Company Liquidity and Share Prices: Empirical Evidence in the Coal Mining Sub Sector in Indonesia - Irpan; Muryani Arsal; Ismail Badollahi (Journal AGENCY, 2026)
This study investigates the effect of corporate liquidity, proxied by the Current Ratio (CR), on stock prices in coal mining sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2022 period. The research is motivated by the strategic importance of the coal industry in Indonesia and the increasing reliance of investors on financial performance indicators in making investment decisions, particularly in the post-COVID-19 economic recovery phase. This study adopts a quantitative approach with an explanatory research design, utilizing secondary data derived from annual financial statements and stock price records. The sample consists of eight companies selected through purposive sampling, resulting in 24 firm-year observations. Data analysis was conducted using simple linear regression, preceded by classical assumption tests including normality and heteroskedasticity tests. The empirical results indicate that the Current Ratio has a positive and statistically significant effect on stock prices, suggesting that higher liquidity enhances investor confidence and firm valuation in the capital market. These findings are consistent with the signaling theory and the semi-strong form of the Efficient Market Hypothesis, which posit that publicly available financial information is rapidly reflected in stock prices. However, this study is limited by its relatively small sample size and the use of a single independent variable. Future research is recommended to incorporate additional financial and macroeconomic variables and apply panel data techniques to provide more comprehensive and robust findings.